Psychosocial Distress in Women With Breast Cancer and Their Partners and Its Impact on Supportive Care Needs in Partners - Goerling, Ute; Bergelt, Corinna; Müller, Volkmar; Mehnert-Theuerkauf, Anja (Frontiers in Psychology, 2020)
Objectives While both patients and informal caregivers report high levels of cancer-related distress, supportive care needs of relatives are often not taken into account and little is known about mutual perception of distress within couples. Therefore, we aimed to investigate distress in female patients with breast cancer and their male partners as well as supportive care needs in partners. Methods In this cross-sectional study, we recruited women with breast cancer during primary cancer care and their male partners, obtained information on mental distress and supportive care needs through visual analog scales for four mood domains and the Short Form of Supportive Care Needs Survey (SCNS-SF34). Results Among 250 eligible patients with breast cancer, 102 patients (40.8%) and their male partners participated. Partners reported higher levels of distress (p = 0.02), whereas patients (self-assessment) indicated stronger needs for help (p < 0.001). Men with higher levels of distress were younger (p < 0.001), and reported a shorter relationship duration (p = 0.001) compared to partners with lower distress. Partners overestimated distress, anxiety, depression, and need for help in the patient. Patients overestimated partners need for help. The majority of partners (78%) reported at least one unmet need, most frequently related to the health system and information domain. Conclusion A systematic distress and needs assessment for women with breast cancer and their male partners is mandatory. The provision of optimal supportive care depends on protocols that include not only psychosocial care for patients but also procedures for managing distress and needs for partners including individual and couple-based interventions.